Dynamin-2 Function and Dysfunction Along the Secretory Pathway - González-Jamett, Arlek M.; Momboisse, Fanny; Haro-Acuña, Valentina; Bevilacqua, Jorge A.; Caviedes, Pablo; Cárdenas, Ana M. (Frontiers in Endocrinology, 2013)
Dynamin-2 is a ubiquitously expressed mechano-GTPase involved in different stages of the secretory pathway. Its most well-known function relates to the scission of nascent vesicles from the plasma membrane during endocytosis; however, it also participates in the formation of new vesicles from the Golgi network, vesicle trafficking, fusion processes and in the regulation of microtubule and actin cytoskeleton dynamics. Over the last eight years, more than twenty mutations in the dynamin-2 gene have been associated to two hereditary neuromuscular disorders: Charcot-Marie-Tooth neuropathy and Centronuclear myopathy. Most of these mutations are grouped in the pleckstrin homology domain; however, there are no common mutations associated with both disorders, suggesting that they differently impact on dynamin-2 function in diverse tissues. In this review, we discuss the impact of these disease-related mutations on dynamin-2 function during vesicle trafficking and endocytotic processes.